Influences of social support following hip-fracture surgery for older adults with cognitive impairment and their family caregivers - Ming-Yueh Tseng; Jersey Liang; Ying-Jen Chen; Chi-Chuan Wu; Yea-Ing L. Shyu (BMC Geriatrics)
Abstract Background Social support can impact family caregivers and influence the care receiver’s recovery from surgery following hospital discharge. This study aimed to explore the influence of perceived social support on outcomes for dyads of older adults with cognitive impairment recovering from hip fracture surgery and their family caregivers. Methods This secondary analysis utilized data from a single-blind clinical trial involving 131 dyads randomly assigned to an intervention or control group. Perceived social support was assessed one month post-discharge using the Medical Outcomes Study Social Support Survey (MOS-SSS) and categorized as good (score = 95) or poor (< 95). Outcomes measured at 1, 3, 6, and 12 months included care receiver-specific outcomes (hip range of motion, muscle strength, nutritional status, depressive symptoms, and health-related quality of life [HRQoL]) and caregiver-specific outcomes (competence, self-efficacy, and HRQoL). The influence of good social support compared with poor social support on outcomes for care receivers and caregivers was analyzed with hierarchical linear modeling as a function of GSS and controlling for covariates of group assignment, pre-fracture activities of daily living of care receivers, and attrition. Results Care receivers with perceived good social support showed significantly better trajectories in hip range of motion, muscle strength, nutritional status, depressive symptoms, and MCS-HRQoL. Caregivers with good social support demonstrated significantly higher PCS-HRQoL and MCS-HRQoL scores, although no differences in caregiver competence or self-efficacy were observed. However, caregivers whose care receivers had good social support exhibited significantly higher competence and self-efficacy at three months post-discharge, with effects sustained over 12 months. Conclusions Good perceived social support positively influenced recovery trajectories for older adults with cognitive impairment and improved HRQoL for both care receivers and caregivers, highlighting the importance of developing targeted interventions to enhance social support during post-surgical recovery for this vulnerable population.